Static and Dynamic Mechanical Properties of Expanded Polystyrene - Chen, Wensu; Hao, Hong; Hughes, D.; Shi, Y.; Cui, J.; Li, Z. (Elsevier, 2015)
Expanded polystyrene (EPS) is commonly used in a variety of applications because of its features of light weight, good thermal insulation, moisture resistance, durability, acoustic absorption and low thermal conductivity. It has been increasingly used in building constructions as core material of structural insulated panels (SIP). Some of those structures during their service life may be subjected to dynamic loads such as accidental or hostile explosion loads and windborne debris impacts. Understanding the dynamic material properties of EPS is essential for reliable predictions of the performances of the structural insulated panels with EPS foam core material. This paper presents static and dynamic compressive and tensile test data of EPS with density 13.5 kg/m3 and 28 kg/m3 at different strain rates. The dynamic strength, Young’s modulus and energy absorption capacities of the two EPS foams at different strain rates are obtained and presented in the paper. Based on the testing data, some empirical relations are derived, which can be used to model EPS properties in numerical simulations of dynamic responses of structural insulated panels with EPS foam core subjected to impact and blast loads.